Zn(II)–curcumin prevents cadmium-aggravated diabetic nephropathy by regulating gut microbiota and zinc homeostasis - Sun, Wenjia; Mei, Xueting; Wang, Jiasheng; Mai, Zhicong; Xu, Donghui (Frontiers in Pharmacology, 2024)
Diabetic nephropathy (DN) is known as the most common complication of diabetes, resulting from a complex inheritance-environment interaction without effective clinical treatments. Herein, we revealed the protective effects and mechanisms of Zn(II)-curcumin, a curcumin derivative, against streptozotocin-induced DN in rats in the presence or absence of cadmium exposure. We found Zn(II)-curcumin significantly mitigated the cadmium-aggravated phenotypes of diabetic nephropathy, as indicated by the remission of renal dysfunction, pathological changes, inflammation and zinc dyshomeostasis in streptozotocin-treated rats exposed to cadmium. Administration of Zn(II)-curcumin significantly alleviated the dysbiosis of gut microbiota and the changes of serum metabolite profiles in rats treated with streptozotocin in combination with cadmium. Notably, fecal microbial transplantation identified the ability of Zn(II)-curcumin to regulate renal function, inflammation and zinc homeostasis was partly dependent on the gut microbiota. These findings revealed that Zn(II)-curcumin alleviated cadmium-aggravated diabetic nephropathy by reshaping the gut microbiota and zinc homeostasis, which provided unique insights into the mechanisms of the treatment and prevention of diabetic nephropathy.